Optical fiber sensor based on Lossy-mode resonance for tamoxifen detection and sensing applications - Fardin Sadeghfar; Roghaieh Parvizi; Moladad Nikbakht (Scientific Reports)
Abstract In this study, we report a novel, eco-friendly optical fiber biosensor for tamoxifen (TAM) detection, featuring a single functional layer of cerium dioxide (CeO2) nanoparticles integrated with a molecularly imprinted polymer (MIP). The CeO2 nanoparticles were synthesized via a green chemistry route using oak fruit extract, yielding nanomaterials with a high refractive index and excellent charge-transfer properties. These unique optical features of CeO2 significantly enhance the lossy mode resonance (LMR) phenomenon by strengthening the fiber’s evanescent field, resulting in improved sensitivity and resonance stability. The MIP, synthesized through a facile, surfactant-free, one-step polymerization of polystyrene spheres, serves as the selective recognition layer, ensuring targeted binding of TAM without interfering with the LMR optical response. The MIP/CeO2 nanocomposite was uniformly coated onto a curved optical fiber surface, and the resulting sensor was thoroughly characterized using FESEM, XRD, AFM, FT-IR, and UV-Vis spectroscopy. These analyses confirmed the successful formation of a porous, TAM-selective MIP layer and the effective incorporation of CeO2 nanoparticles. The sensor demonstrated rapid adsorption/desorption kinetics and high permeability, enabling swift and sensitive TAM detection. Under optimal conditions, the LMR-based fiber optic sensor achieved a sensitivity of 12.052 nm/ $$\upmu$$ M with a correlation coefficient (R2) of 0.988. The proposed biosensor shows strong potential for sensitive, selective, and sustainable detection of tamoxifen in pharmaceutical and clinical applications.